Effectiveness of Different Probiotic Application on Vannamei Shrimp Productivity - Maria Goreti Eny Kristiany; Guntur Prabowo; Suharyadi Suharyadi; Erni Marlina (Jurnal Perikanan Universitas Gadjah Mada, 2022)
Vannamei is a superior commodity of aquaculture in Indonesia. However, production of vannamei only reached 91.5% of the 450.000 tons revised target. Several factors are the cause of the target not being achieved. One of which is a disease outbreak. The use of probiotics as an application that improves the health status of shrimp is a better choice than the use of antibiotics for treatment. The effectiveness of the application of probiotics to control pathogenic microorganisms is highly influenced by the type of bacteria used. This research was conducted to examine the efficacy of using two different types of probiotics with different bacteria compositions on the productivity of vannamei shrimp. The 2.200 m2 pond plots shielded with low-density polyethene (LDPE) were used. The stocking density was 250 fry.m-2. The vannamei shrimp were fed with an artificial diet containing protein from 30-40%, fat form 5%, fibre form 4%, and water content form 11% during rearing. In preparation and maintenance of water management, probiotics A and B. were applied. The results showed that the use of type B probiotics reached better productivity than type A.